Dynamization of the Reprimand Model in the Independent Curriculum for Children 6-12 Years of Age in Primary Schools in Indonesia - Wahyu Ariaini; Rut Sanaya; Santori; Yeyen (PT FORMOSA CENDEKIA GLOBAL, 2023)
Reprimands generally carry multiple perceptions. These perceptions frame the subject and can become a habit. The habit of the large portion of reprimands compared to rewards should bring students to a psychological pressure. The author looks at the understanding of this reprimand model in the location of students in one of the Palangka Raya Cities. The purpose of this study is to explore the reprimand model in the current curriculum for students aged 6-12 years in one of the elementary schools in Palangka Raya city. This research approach is qualitative research with interview techniques. The results of recording interviews, the author poured in transcripts and factual solids. The results showed that punishment and reward are in accordance with their portions. As a result, teachers and students are free to find their own potential. Teachers are free to choose teaching tools that are suitable for students. Students—In the context of the curriculum—develop according to their capacity in the learning process.